Virtual Economy Simulation Model (VESM): Interactive Learning Innovation in Introductory Economics Courses - Endah Andayani; Della Rulita Nurfaizana; Udik Yudiono; Lilik Sri Hariani; Fonny Dameaty Hutagalung (Journal of Economic Education and Entrepreneurship Studies, 2026)
The development of digital technology has driven learning innovation in the Introduction to Economics course, especially in vocational education. This study aims to develop a Virtual Economy Simulation Model (VESM) as an interactive learning medium based on scenario-based learning designed to improve the market analysis skills of 70 students of Office Administration Education, Offering A and E, class of 2024. The research method uses the Borg & Gall Research and Development (R&D) model modified into seven stages, including needs analysis, design, prototype development, expert validation, limited trials, field trials, and product revisions. The research instruments include economic knowledge tests, market analysis task performance, and a System Usability Scale (SUS) questionnaire. The content validity results show a CVI of 0.89 (high category). The field trial resulted in a significant increase in pre-test to post-test scores in both groups with an N-gain of Offering A of 0.63 while Offering E was 0.66 with an effect size of Cohen's d = 1.59. The average SUS score reached 86.2 (excellent), while qualitative data showed that 92% of students considered VESM to be helpful in understanding economic concepts realistically. These findings indicate that VESM is effective in improving market analysis skills, learning engagement, and theory-practice integration. This model has the potential to be widely adopted in economics teaching in higher education.